High Li-ion conductivity of Al-doped Li7La3Zr2O12 synthesized by solid-state reaction - Hu, Zhongli; Liu, Hongdong; Ruan, Haibo; Hu, Rong; Su, Yongyao; Zhang, Lei (Ceramics international, 2016)
Li7La3Zr2O12 (LLZO) has cubic garnet type structure and is a promising solid electrolyte for next-generation Li-ion batteries. In this work, Al-doped LLZO was prepared via conventional solid-state reaction. The effects of sintering temperature and Al doping content on the structure and Li-ion conductivity of LLZO were investigated. The phase composition of the products was confirmed to be cubic LLZO via XRD. The morphology and chemical composition of calcined powders were investigated with SEM, EDS, and TEM. The Li-ion conductivity was measured by AC impedance. The results indicated the optimum sintering temperature range is 800–950°C, the appropriate molar ratio of LiOH·H2O, La(OH)3, ZrO2 and Al2O3 is 7.7:3:2:(0.2–0.4), and the Li-ion conductivity of LLZO sintered at 900°C with 0.3mol of Al-doped was 2.11×10−4Scm−1 at 25°C.